Kingdom of the blazing phoenix - Dao, Julie C. (Dao, Julie C. Rise of the empress, 2019)
All Jade wants is a quiet, simple life. But as the daughter of the Emperor of Feng Lu, she knows she can't sit idly by while her kingdom falls to ruins and her people's lives are destroyed. It's time for Jade to stand up to the person who wanted her out of the way in the first place: the beautiful and powerful Xifeng. Can Jade survive her evil stepmother's machinations and regain control of her land?